Optimization of 3D Printing Process Parameters of Polylactic Acid Filament Based on the Mechanical Test - S. Raja; Anant Prakash Agrawal; Pravin P Patil; P. Thimothy; Rey Y. Capangpangan; Piyush Singhal; Mulugeta Tadesse Wotango (International Journal of Chemical Engineering)
The main objective of this research study is to optimize the printing parameters that can be used in the FDM (fusion deposition modeling) production method to obtain the lowest production time and best printing parameter of PLA (polylactic acid) filament with the tensile test. The printing parameter that can be used in FDM machines such as extruder temperature, bed temperature, layer height, printing speed, travel speed, infill, and shell count is taken into account for optimization. In addition, the tensile specimens from ASTM (American Society for Testing and Materials) D638 standard were manufactured by PLA filament with the above-modified printing parameters. The best printing parameters for PLA products were found by the time recorded during production and tensile test results after production. Thus, through this research, one can find the best PLA filament printing parameters and their timing.